ISOLASI DAN IDENTIFIKASI BAKTERI PENYEBAB PENYAKIT BUSUK LUNAK PADA BUAH STROBERI (Fragaria x ananassa) - Yuliasari, Made Mega; Kawuri, Retno; Proborini, Meitini Wahyuni (Metamorfosa: Journal of Biological Sciences; Vol 2 No 1 (2015), 2015)
Soft rot on strawberry fruit was found in strawberry ( F . x ananassa ) plantation in Candi Kuning, Bedugul, Bali. Soft rot on strawberry fruit can be caused by microorganism i.e. bacteria. Objectives of the research were to isolate pathogen causing soft rot on strawberry fruit with plating method and to identify bacteria causing soft rot by using Kit Microgen TM GNA+B-ID System and Bergey’s Manual of Determinative Bacteriology reference (Holt et al. , 1994). Results showed there were five isolates of bacteria (IB-1, IB-2, IB-3, IB-4, and IB-5). Positive result of Postulat Koch showed that bacteria causing soft rot on strawberry is IB-1. Identification that was done by using Kit Microgen TM GNA+B-ID System and Bergey’s Manual of Determinative Bacteriology reference (Holt et al. , 1994), showed that the isolate IB-1 is Weeksella
Keywords: identification, soft rot, strawberry fruit, Weeksella